Social context modulates food hoarding in Syrian hamsters (2016)
The effect of the presence of a con-specific in the temporal organization of food hoarding was studied in two varieties of Syrian hamster (Mesocricetus auratus): golden and long-haired. Four male hamsters of each variety were used. Their foraging behavior was observed during four individual and four shared trials in which animals were not competing for the same food source or territory. During individual trials, long-haired hamsters consumed food items directly from the food source, transporting and hoarding only remaining pieces. During shared trials, the long-haired variety hoarded food items before consumption, and increased the duration of hoarding trips, food handling in the storage, and cache size. Golden hamsters maintained the same temporal organization of hoarding behavior (i.e., hoarding food items before consumption) throughout both individual and shared trials. However, the golden variety increased handling time at the food source and decreased the duration of hoarding trips, the latency of hoarding and storing size throughout the shared trials. In Syrian hamsters, the presence of a con-specific may signal high probability of food source depletion suggesting that social pressures over food availability might facilitate hoarding behavior. Further studies are required to evaluate cost-benefit balance of food hoarding and the role of cache pilferage in this species.